2016
DOI: 10.1186/s40337-016-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural context of eating disorders in Poland

Abstract: BackgroundThe goal of this study was to assess the relationship between sociocultural factors and clinical eating disorders during the intensive process of Westernisation in Poland that occurred after 1989. The study population included girls diagnosed with an eating disorder according to DSM-IV criteria (n = 47 anorexia nervosa restrictive type [ANR], n = 16 anorexia binge/purge type [ANBP], n = 34 bulimia nervosa [BN], n = 19 eating disorder not otherwise specified [EDNOS]) who received consultation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…Analysis of the source literature confirms the continual increase of the number of people suffering from eating disorders worldwide [1,2]. Epidemiological data confirm the increasing importance of the problem in European countries [3,4], including Poland [5,6], the United States of America [7], Latin America [8], Arab countries [9,10], Africa [11], and Asia [12][13][14][15][16], with the risk of development of eating disorders being especially high in Japan [17]. The Global Burden of Disease (GBD) study from 2015 [18] confirmed the steady increase of eating disorders in women all around the world [19].…”
Section: Epidemiology Of Eating Disordersmentioning
confidence: 71%
See 1 more Smart Citation
“…Analysis of the source literature confirms the continual increase of the number of people suffering from eating disorders worldwide [1,2]. Epidemiological data confirm the increasing importance of the problem in European countries [3,4], including Poland [5,6], the United States of America [7], Latin America [8], Arab countries [9,10], Africa [11], and Asia [12][13][14][15][16], with the risk of development of eating disorders being especially high in Japan [17]. The Global Burden of Disease (GBD) study from 2015 [18] confirmed the steady increase of eating disorders in women all around the world [19].…”
Section: Epidemiology Of Eating Disordersmentioning
confidence: 71%
“…Analysis of the literature suggests that the basic risk factors of eating disorders are directly related to the development of personal dissatisfaction with one's body, excessive pursuit of thinness, and restrictive and bulimic eating behaviours, and this relationship is noted by authors conducting research in both Western cultures [1], including Poland [6,42], and Eastern cultures [13] such as Japan [17,43]. According to the literature from the last several years, people who suffer from anorexia or bulimia are dissatisfied with their bodies and are characterized by excessive perfectionism and a desire for control.…”
Section: Risk Factors For Eating Disordersmentioning
confidence: 99%
“…Disordered eating patterns represent eating related unhealthy behaviors (e.g., excessive concern about weight and shape, excessive dieting, self-induced vomiting) that resemble Eating Disorders (ED) but are exhibited in a smaller degree in terms of frequency and intensity (1). Traditionally believed to be affecting women of affluent societies (2, 3), the prevalence of EDs has been increasing among diverse populations and cultures (4–8). While researchers are trying to find out more about the main determinants, risk and protective factors of EDs, it is recognized that they are culturally influenced (913).…”
Section: Introductionmentioning
confidence: 99%
“…The link between culture change and disordered eating has attracted researchers’ interest towards the end of the twentieth century as EDs started emerging in non-Western countries, including Eastern Europe, and among immigrant/minority populations (8, 26–29). Cases of EDs in some parts of the world, e.g., the island of Curacao and South America, appeared very low primarily affecting elite groups exposed to North American and European influence (14, 27, 30), which further strengthened the hypothesis linking EDs with acculturation to Western culture and values.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of the Pro ana movement, where the participants of the movement try to give a new meaning to the concept of normal weight, in which thinness should be accepted as a normal range, while they determine their health status as a lifestyle, demanding acceptance for their own choices (54). As Maciej W. Pilecki, Barbara Józefik and Kinga Sałapa draw attention, due to such "phenomena" eating disorders cease to be perceived as a disease, and they become an expression of personal transgression, selfcreation supported by other participants of such movements (55).…”
Section: Resultsmentioning
confidence: 99%